Women Preparing to Re-Enter the Workplace - Shapiro, Marion; Fitzsimmons, George (Canadian Journal of Counselling and Psychotherapy, 2011)
Re-entry women have been conceptualized as a homogeneous group primarily due to their highly similar personality and demographic characteristics. Divorced, widowed, and separated women as well as low income women are increasingly found within re-entry populations. However, little is known about how these women may differ from the other subgroups of reentry women. To this end, the personality characteristics, life events, and work values of three subgroups of re-entry women were studied (Adapters, Explorers, Change Seekers). Results indicated that similarities and differences do exist within the re-entry population. The personality characteristics commonly ascribed to re-entry women as a group were not the same as those personality characteristics found to be significant among the three groups of re-entry women. Significant differences were found between subgroups on the Life Events Scale and on six of the twenty work values. The implications for career counselling are discussed.